The Four Ariya-saccas as ‘True Realities for the Spiritually Ennobled’- the Painful, its Origin, its Cessation, and the Way Going to This – Rather than ‘Noble Truths’ Concerning These - Harvey, Peter (Buddhist Studies Review, 2009)
This paper critiques the standard translation of ariya-sacca as ‘Noble Truth’ and argues that the term refers to four saccas as ‘true realities’, rather than as verbalised ‘truths’ about these realities; the teachings about them are not, as such what the term ariya-sacca refers to. Moreover, only one of the ariya-saccas (the fourth) is itself ever described in the suttas as ‘noble’. The four are ‘true realities for the spiritually ennobled’: the fundamental, basic, most significant genuine realities that the Buddha and other noble ones see in the flow of experience of themselves and/or others. The first of them is not best translated as ‘suffering’ but as ‘pain’ – in all its many senses – or indeed ‘the painful’: the upadana-kkhandhas as ‘bundles of grasping-fuel’ which are described, adjectivally, as ‘painful’. The paper includes a new translation of the Dhamma-cakka-ppavattana Sutta in line with this analysis